The Role of Wonderful Indonesia Website in Supporting Digital Tourism Marketing: Performance Analysis and Its Impact - Asep Koswara (International Journal of Tourism Management and Hospitality, 2025)
This study examines the role of the Wonderful Indonesia website (www.indonesia.travel) in supporting digital tourism marketing and its impact on foreign tourist arrivals. Utilizing a descriptive quantitative approach, the research analyzes the website's performance using digital marketing tools, specifically app.neilpatel.com, to evaluate key metrics such as website traffic, SEO performance, and keyword rankings. The study reveals that the website has achieved significant organic traffic, generating 6 million organic visitors and maintaining a strong domain authority score of 69. Popular keywords including "Indonesia," "Labuan Bajo," "Sanur Bali," and "Bromo Mountain" rank highly in search results, driving substantial traffic to the site. Analysis of monthly traffic data from September to December 2024 shows a gradual decrease in visits from 11.5 million to 6.4 million, although the website maintained significant engagement throughout this period. The research correlates these digital metrics with data from Badan Pusat Statistik (BPS), which reported corresponding declines in foreign tourist arrivals during the same period. Despite the website's high traffic and strong digital presence, the findings suggest that digital marketing efforts alone may not be sufficient to convert website visits into increased tourist arrivals, indicating the need for an integrated approach to digital marketing strategies.